Multimodalna analiza protestów antycovidowych z 2020 r. w Polsce = Multimodal analysis of the anticovid protests of 2020 in Poland - Wiśniewski, Patryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to prove the multimodality of anticovid protests in Poland. Therefore, four areas related to the issue of manifestation were examined: spatial, audial, visual and verbal sphere. The research material, based on photos as well as professional and amateur recordings, was selected on the basis of observation of the demonstrations in 2020. The analysis proved the multimodality and multidimensionality of the anticovid protests, and also drew attention to the heterogeneous nature of the community od its participants.
Keywords: pandemia; koronawirus; protest antycovidowy; analiza multimodalna; pandemic; coronavirus; anticovid protest; multimodal analysis